The Violation and Flouting of Cooperative Principles in the Ellen Degeneres Talk Show - Zebua, Esterani; Rukmini, Dwi; Saleh, Mursid (Universitas Negeri Semarang, 2017)
This study is pragmatic studies. It aimed at investigating the violation and fluoting of quantity maxims, quality maxims, relevan maxims, manner maxims were used by male and female participants in the Ellen DegeneresTalkshow. The violations of maxims occur when the maxims are deliberately manipulated so that the speaker misleads the interlocutor. While the flouting of maxims occurs when individuals intentionally do not apply the maxims in order to persuade their listeners to derive the hidden meaning behind what is said, that is, the speakers employ implicature. In obtaining the data, the researcher uses the descriptive qualitative to the utterances of sixteen guests stars which is devided in to eight male and eight female. The data is taken from six episodes in the newest edition in 2016. The result reveals that the male participants mostly did the flouting than violating. From the overall of violation and flouting they done, quantity maxim is dominantly flouted by male participants. Based on the analysis it signed that male partcipants mostly uses exaggerated statement to convey their opinion which is too strong and appears worse than the really they are. They gave more explanations in order the audience satisfied and to comfirmed the real information toward the negative thinking of audience at the previous time while the female participants dominantly violate the maxim of relevance. The female participants tend to avoid talking about something. They change the topic of conversation and do not give well responses to the partner.